Factors Affecting Green Growth Policy in Vietnam - Trung, Phan Nhan (PT. Riset Press International, 2025)
Green growth is becoming a global priority as countries increasingly recognize the importance of combining economic development with environmental protection. Green growth policies and strategies are designed to reduce greenhouse gas emissions, promote the use of renewable energy, and improve resource efficiency, contributing to the goal of sustainable development and combating climate change. Government green growth policies are influenced by many economic, social, environmental, and political factors that determine the effectiveness and sustainability of these measures. Essential factors include public awareness, international pressure, economic and financial policies, technology and innovation, local environmental issues, politics and leadership, and public-private partnerships (PPPs). Vietnam has implemented the